Controle químico do melanaphis sorghi (Theobald) (Hemiptera: Aphididae) na cultura do sorgo - Costa, Guilherme Hugo da Silva (2022)
Sorghum bicolor (L.) Moench is the fifth most important cereal in the world in cultivated area. Brazilian production was estimated at 3,065 million tons in the 2021/22 harvest. Due to the high infestation of the aphid Melanaphis sorghi (Theobald,) 1904, (Hemiptera: Aphididae) in the sorghum crop in the last seasons, the production of this cereal has been compromised. This study aimed to evaluate the efficiency of insecticides in controlling M. sorghi in sorghum under field conditions. The experiment was installed in the experimental area of the Glória UFU – MG campus. An experimental design was used in randomized blocks with seven treatments and four replications, totaling 28 plots. The plots were composed of six rows spaced 0.5 m apart, 5 meters long and density of 10 seeds per linear meter. The sorghum cultivar K 200 was used, it was sown on March 14, ten days after the emergence of the plants, the aphids were distributed in the area. The treatments were: Control; Mospilan (acetamiprid) (350 g p.c/ha); Nuprid 700 WG (imidacloprid) (100 g p.c/ha); Nortox Acephate (acephate) (1000 g p.c/ha); Engeo plena S (cylorin lick + thiamethoxam) (250 ml p.c/ha); Talisman (bifenthrin + carbosulfan) (700 ml p.c/ha); Sperto (acetamiprid + bifenthrin) (120 g p.c/ha). Two insecticide applications were carried out, when the number of aphids reached the control level. Evaluations were performed at zero (prior), four, six and eight days after application (D.A.A). All insecticides were efficient in controlling M. sorghi. The insecticide Engeo Pleno S followed by the insecticide Nuprid 700 WG showed a greater residual effect.